Seakeeping and Safety Assessment of Fishing Vessel 30 GT - Rizky Irvana; Arif Fadillah; Shanty Manullang (International Journal of Marine Engineering Innovation and Research, 2022)
In Indonesia, many fishing vessels are made from generation to generation in a traditional way. As a result, the ships built did not comply with the regulations and permits of the naval architects. The fishing industry is one of the most dangerous because it works on the high seas. Therefore the performance in hydrodynamics and safety should be evaluated on these traditional vessels. The main objective of this research is to evaluate the hydrodynamic performance and safety of fishing vessels. Following standard specifications or criteria, seakeeping performance is evaluated using Maxsurf Ship Design software. Assessment of existing safety equipment uses IMO (International Maritime Organization) regulations and the Torremolinos protocol. As a result, the ship can only operate at a wave height of 0,1-0,5 meters or undersea state 3. Ship safety inspections reveal that they still do not meet the required requirements and do not have the necessary equipment specified by the World Maritime Organization (IMO).